Effect of chemical treatments on the mechanical properties of technical flax fibres with emphasis on stiffness improvement. (26th May 2018) - Perremans, D.; Hendrickx, K.; Verpoest, I.; Van Vuure, A.W.
Abstract: The weak visco-elastic interphase between elementary fibers in a reinforcing technical flax fiber is presumed to play a crucial role in the stiffness reduction during loading. To avoid this stiffness reduction, ethanedial (glyoxal), 3-aminopropyltriethoxysilane (APS) and dimethyloldihydroxyethylene urea (DMDHEU) were investigated as potential fiber treatments in this paper. Tensile tests on single technical fibers show that treating the fibers in an aqueous 3 wt% glyoxal solution was sufficient to increase the technical fiber modulus from 41.6 ± 2.3 GPa to 57.3 ± 2.9 GPa. Further, spectroscopic techniques (FTIR, NMR and XPS) detected increased amounts of acetal and ester bonds after glyoxal treatment. This suggests that cross-linking has taken place between pectin and hemicellulose molecules in the amorphous interphase between elementary fibres. APS and DMDHEU treatments were less successful in improving the technical fibre stiffness due to their lower reactivity towards hydroxyl functionalities compared to glyoxal.